The ‘New’ Norms of Education Policy in the 21st Century: Polemics, Pandemics, and ‘Cloaking’ Persistent Inequality in Education Worldwide: English - Wiseman, Alexander (Revista Española de Educación Comparada, 2021)
The 21st century has brought policy change to education at levels rivaling the paradigm-shifting global educational reform efforts of the 20th, but the same problems (in different forms) seem to be repeating nonetheless. 21st century education policy, especially at the global and national levels is forced to recognize and address the effects of a pandemic, polemical and populist politics, and both institutionalized sexism and racism. And, there have been and will continue to be significant changes in 21st century education policy and practice in response to these crises, but amid the change there is remarkable permanence in the 20th century ideas, structures, content, and pedagogy embedded in education as well. This paper examines the promise of 20th century advances in education policy and practice against the challenges and pitfalls of 21st century education as evidenced by national and international educational developments